In vitro biodegradation of bacterial nanocellulose under conditions simulating human plasma in the presence of selected pathogenic microorganisms - Dederko, P.; Malinowska-Pańczyk, E.; Staroszczyk, H.; Sinkiewicz, I.; Szweda, P.; Siondalski, P. (Polimery, 2021)
The biodegradability of bacterial nanocellulose (BNC) was assessed based on a change in its properties under conditions simulating human plasma in the presence or absence of the pathogens Staphylococcus aureus, Candida albicans and Aspergillus fumigatus. It was shown that the dry mass of BNC did not change during 6 months of incubation, except for samples stored in the presence of moulds, where the dry mass reduced by 40%. The wet mass of all BNC samples increased after 2 months of incubation. Under these conditions, the population number of microorganisms grew about 2 log cycles during the first month and maintained this level for 6 months of storage. After 1 month of storage in sterile fluids, and in the presence of bacteria or fungi, the tensile strength of BNC decreased by 60% or 70%, respectively.